Capacity, Competency, and Courts: The Illinois Experience - Wenona Y. Whitfield (Washington University Journal of Law & Policy, 2004)
This Essay examines decisions involving involuntary medication in Illinois over the past decade, with a particular emphasis on how judges decide whether the patient has the capacity to refuse medication. The author concludes that Illinois courts have demonstrated an inability to decide questions of competency, and that a more efficient system that protects the rights of mental health patients is needed. Part I briefly surveys the present statutory scheme in Illinois and in other states that have chosen a judicial model for deciding questions of a patient’s competency to refuse psychotropic medication. Part II analyzes appellate decisions from Illinois, emphasizing the inability of judges to articulate a standard for competency. Part III concludes with a proposal for amending the legislative standard for determining competency and suggests an alternative model for determining competency of patients refusing psychotropic medication.
Keywords: Involuntary treatment; Psychotropic drugs; Patients -- Civil rights; Patient refusal of treatment; Medicine -- Decision making; People with mental disabilities